2018
DOI: 10.1021/acs.analchem.8b04045
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Assay of the Alpha Fetoprotein-L3 Isoform Ratio To Improve the Diagnostic Accuracy of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is now the major malignant disease with high morbidity and mortality, which seriously endangers human lives and health. Alpha fetoprotein (AFP) assay is a commonly used serological biomarker for clinical diagnosis of HCC, but it lacks specificity. Analysis of its isoform AFP-L3, especially the AFP-L3 ratio in total AFP (AFP-L3%), can significantly improve the specificity for HCC identification. Herein, an electrochemical approach has been first proposed for simple, accurate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Treatment with LUT suspension does not affect the hepatic GPC3 gene expression. After treatment with LUT-ENPs, the hepatic GPC3 gene expression was significantly decreased in comparison to carcinogenic groups ( p < 0.05) [ 55 , 56 ] ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with LUT suspension does not affect the hepatic GPC3 gene expression. After treatment with LUT-ENPs, the hepatic GPC3 gene expression was significantly decreased in comparison to carcinogenic groups ( p < 0.05) [ 55 , 56 ] ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with LUT suspension does not affect the hepatic GPC3 gene expression. After treatment with LUT-ENPs, the hepatic GPC3 gene expression was significantly decreased in comparison to carcinogenic groups (p < 0.05) [55,56] (Figure 7). By comparing the data obtained from carcinogenic groups and healthy groups w found that liver biomarkers, total bilirubin, and AFP-L3 were significantly elevated in th carcinogenic groups (p < 0.05) with respect to healthy groups.…”
Section: Gene Expression Levels Of Gpc3 By Rt-pcrmentioning
confidence: 96%
“…In addition, AFP-L3 can be used in the monitoring of disease prognosis. The Food and Drug Administration has approved the use of AFP-L3 as an early diagnostic marker for HCC, with 10% of total AFP content as a positive crucial value because this ratio elucidates an incidence of over 95% for HCC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AFP-L3 can be detected in the serum 9–12 months before the detection of tissue lesions by screening. Finally, AFP-L3 can be used to determine disease prognosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the electrochemical sensors based on coinage (gold, silver, and copper) nanomaterials with versatility have been developed [42]. In particular, the copper nanoparticles (CuNPs) as electrochemical reporters possessed the virtue of affordable price and unique electrochemical properties [43]. The oxidation of CuNPs could provide plentiful Cu 2 + and thus ultra-sensitive detection could be obtained.…”
Section: Introductionmentioning
confidence: 99%